The Modern Satiric Grotesque and Its Traditions - Clark, John R., 1930- (Book collections on Project MUSE., 1991)
Thomas Mann predicted that no manner or mode in literature would be so typical or so pervasive in the twentieth century as the grotesque. Assuredly he was correct. The subjects and methods of our comic literature (and much of our other literature) are regularly disturbing and often repulsive -- no laughing matter. In this ambitious study, John R. Clark seeks to elucidate the major tactics and topics deployed in modern literary dark humor. In Part I he explores the satiric strategies of authors of the grotesque, strategies that undercut conventional usage and form: the de-basement of heroes, the denigration of language and style, the disruption of normative narrative technique, and even the debunking of authors themselves. Part II surveys major recurrent themes of grotesquerie: tedium, scatology, cannibalism, dystopia, and Armageddon or the end of the world.